The Commemoratio pro vivis of the Roman Canon: a textual witness to the evolution of Western Eucharistic theologies? - O'Loughlin, Thomas (Peeters, 2014)
This text - an important element in the Western Latin Eucharistic Prayer - has not been studied in detail since the 1950s (Jungmann); and has never been studied using the methods of modern textual studies. Yet it bristles with problems - textual variations in the early witnesses; theological in that the argument is self-contradictory; and linguistic: the Latin syntax is not only 'difficult' but downright wrong - which, if noted at all, tend to be ignored. This paper proposes that we see this text as the product of layers of accretion which each layer can be identified and the manner in which its addition distorted the overall text explained by the concerns of specific groups and periods. Having identified the layers, one can then see the original text which has elements that can be paralleled in second-century CE texts. When this Urtext is compared with the later 'textus receptus' it becomes clear that the focus of the text has been completely transformed - and in this transformation of its intent (both as a ritual object and as a text carrying doctrinal weight) lies the source of many later controversies - some of which are still being pursued with vigor today.